Impact of the power-controlled static synchronous machine on transient stability of power system - Qing, Liu; Zheren, Zhang; Yicheng, Xue; Zheng, Xu (Frontiers in Energy Research, 2024)
Compared with the grid-following (GFL)-converter-interfaced generations (CIG), the powercontrolled static synchronous machine (PCSSM) can realize voltage and frequency control through the power tracking function, which has the potential to improve the transient stability of the power system. However, the evolution trend of transient stability of power systems with integrated PCSSM is still unknown. This paper studies the transient stability characteristic of power systems after replacing synchronous generators (SGs) with the PCSSM. The PCSSM and GFL-CIG are integrated into the New England IEEE 39-bus test system, respectively. Firstly, we compare the transient stability of the PCSSM-integrated system with the GFL-CIG-integrated system by changing CIG's integration proportions and locations. Then, the impact of equivalent inertia coefficient J and damping coefficient D on the transient stability of the PCSSM-integrated system is analyzed. Finally, the advantages of PCSSM compared to GFL-CIG are compared and summarized.